Censorship persecution of the kazakh book of the spiritual content - Shalgynbai, Zh; Albekov, T; Saltakova, Zh; A Oralbek, N Yelesbai (Opción, 2019)
The article deals with the issues of censorship of the Kazakh printed book of Muslim spiritual content of the XIX - early XX centuries. As a comparative qualitative research method, the activity of the main censorship department of Tsarist Russia on the restriction of the national book publishing of Turkic peoples of the empire is shown. As a result, the total number of works in the Kazakh language, which were banned for publication and republishing, is more than ten titles. In conclusion, the national book publishing resulted in logical consequences in the form of attempts to organize illegal publishing.